Enhancing Cr(VI) bioreduction via Na+-stimulated intracellular energy metabolism and electron transfer using methane as electron donor - Lianfu Liang; Xiaofeng Fu; Yuqing Ding; Keying Liu; Rui Lin; Zhaojin Chen (Bioresource Technology, 2027)

Biochar enhances anaerobic oxidation of methane coupled with Cr(VI) reduction: Pyrolysis temperature-dependent electron transfer pathways and regulatory mechanisms - Lianfu Liang; Yepu Li; Xiaofeng Fu; Rui Lin; Keying Liu; Zhiqiang Zhao (Bioresource Technology, 2026)

Inside-out conversion of open pores into closed nanopores enables high-plateau hard carbon anodes for sodium-ion batteries - Zhuo Xiong; Rui Li; Ping Liu; Shuang Lin; Chaoshu Zhao; Wenyuan Fu; Jiale Shen; Lili Xiao; Xuedan Chen; Jianping Long; Xianguang Zeng; Anjun Hu; et al. (Chemical Engineering Journal, 2026)

Occurrence and leaching of per- and polyfluoroalkyl substances in waste incineration residues: Insights into thermodynamic mechanisms and implications for environmental release - Lanlan Fu; Xingyao Huang; Xuemei Liu; Nan Zhang; Rui Ma; Xinyue Wang; Yue Zhi; Lin Li; Xiaoming Wang (Journal of Hazardous Materials, 2026)

Exploring the mechanism of platycodon grandiflorum saponins in treating Mycoplasma pneumoniae pneumonia based on intestinal microbiota and metabolomics - Rui Shuang Ji; Yun Fei Yang; Chan Yu Wu; Zhen Jing Yang; Jin Zhao Du; Jing Huang Fu; Lin Yao; Wei Ming Wang (Food Bioscience, 2026)

Autophagy-augmenting peptide nanoplatform for synergistic chemo-immunotherapy against breast cancer - Chen Wei; Wei Gao; Xingyue Li; Ming Fu; Fantao Lin; Xiaoyu Zhao; Huiying Jia; Kang Zhang; Changgang Sun; Rui Wang; Jingkun Bai (Chemical Engineering Journal, 2026)

Effect of the thickness of overlying soil on the location of trailing edge cracks in soil–bedrock landslides induced by water softening - Yun-kang Rao; Jia-xin Chang; Hai-ying Fu; Tao Yang; Huai-lin Chen; Zhe Zhang; Yi Yang; Rui Huang (Bulletin of Engineering Geology and the Environment, 2026)

The potential mechanism of nitrous oxide accumulation in wastewater treatment plants under different load conditions - Wen-Jiao Sang; Bing Gong; Chong-Yang Xing; Bei-Bei Chen; Zhi-Lin Zhang; Hui-Min Fu; Ya-Song Chen; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Yu-Lin Wang; Qiang Wang; et al. (International Biodeterioration & Biodegradation, 2026)

SYVN1-provoked RASA1 ubiquitination promotes pulmonary inflammation in chronic obstructive pulmonary disease - Ju-Hong Wu; Yi-Cheng Ma; Yu-Qi Wang; Hai-Long Miao; Meng-Xue Liu; Dong-Xu Hua; Min-Min Tang; Tian-Rui Sui; Zhi-Yong Wu; Yu Wang; Jin Yang; Hui Zhao; et al. (Inflammation Research, 2026)

Amorphous/crystalline heterophase induced S2− migration and oxidation for enhanced oxygen evolution reaction - Yue Huang; Jiejie Li; Yu Liu; Ying-Jie Ma; Lin Zhu; Fu-Rui Teng; Ziqi Tian; Ai-Dong Li (Chemical Engineering Journal, 2026)

Strong and liquid-free ion-conductive elastomer reinforced by chemically cross-linked cellulose network for strain sensors and triboelectric nanogenerators - Meilin Zhang; Zhongshen Cai; Yufan Lan; Zongming Lv; Rui Qian; Zhongsheng Shi; Lihua Fu; Baofeng Lin; Chuanhui Xu; Qunyang Li; Bai Huang (Chemical Engineering Journal, 2026)

Impact of habitat biotic factors on selective food hoarding in Brandt's voles - Shan-shan Sun; Tao Liu; Hai-rui Yang; Zhi-liang Zhang; Ya-nan Li; Ming Ming; Hao-ting Zhang; Hai-wen Yan; Xin Li; Lin-lin Li; Na Zhu; Xiao-dong Wu; et al. (Journal of Arid Environments, 2026)

The light side of the microbiome in trauma: Mechanism and applications - Han-Yue Luo; Lei-Ming Cao; Kan Zhou; Yi-Fu Yu; Yao Xiao; Guang-Rui Wang; Bing Liu; Qiu-Ji Wu; Xiao-Long Wang; Zhi-Yong Song; Lin-Lin Bu (Chemical Engineering Journal, 2026)

Geochemistry of tourmaline in granitic rocks from the Zharigana and Caolong areas, Northern Tibet: Implications for the identification of lithium-mineralizing plutons - Ling Ma; Jin-Sheng Zhou; Qiang Wang; Lin Ma; Jin-Heng Liu; Wu-Fu Li; Bing-Zhang Wang; Chun-Tao Wang; Jian-Dong Liu; Xin-Yuan Zhang; Mao-Rui Liu; Zhi-Wei Yu; et al. (Lithos, 2026)

Hybrid crested porcupine optimizer decomposition method and deep neural network to predict long-term rainfall - Man-Hong Fan; Xiao-Ying Ma; Shi-Qi Xu; Rui-Lin Fu (Theoretical and Applied Climatology, 2026)

From SPP to RTK: promoting the satellite navigation potential of acoustically excited antenna - Shangyang Wang; Yifan Fu; Rui Hu; Du Li; Bing Xu; Ruofan Liu; Yinuo Song; Junru Li; Bin Fang; Wenkui Lin; Zhongming Zeng; Xiangwei Zhu (GPS Solutions, 2026)

Breaking the trade-off: Trichoderma effector Tahfb1 dual-targets growth and defense pathways via Hsp70L - Yaping Yin; Yuhang Fu; He Wu; Liping Feng; Lijuan He; Runmao Lin; Rui Wang; Zhengbin Tang; Baoping Zhu; Jumei Hou; Jing Zhao; Tong Liu (Pesticide Biochemistry and Physiology, 2026)

Body size- and water homeostasis-dependent temperature stress tolerance and transcriptional changes in red fire ant workers - Wei Gao; Rui Peng; Jian-min Yang; Jian-lin Lu; Hong-yun Cao; Ying-huan Li; Chun Li; Wen Fu; Jin Xu (Journal of Asia-Pacific Entomology, 2026)

Multi-Feature and Multi-Step Monthly Rainfall Forecasting with the Hybrid VMD-LSTM-CATNet Model in Diverse Climatic Regions - Man-Hong Fan; Xiao-Ying Ma; Shi-Qi Xu; Rui-Lin Fu; Zhong-Xing Tao (Water Resources Management, 2026)

A multi-stimuli-responsive supramolecular polymer from γ-Cyclodextrin and Viologen for dual-mode display and ammonia/amines sensing - Dong-Xue Xia; Chen-Yan Xu; Dan-Xuan Pan; Ming-Fu Ye; Rui-Lian Lin; Jing-Xin Liu (Chemical Engineering Journal, 2026)

Defect passivation with Pb for high-performance Sb2S3 solar cells via vapor transport deposition - Gan Huang; Xin-Yi Cai; Hu Li; Jin-Rui Cai; Ying-Sen Xia; Zhi-Ping Huang; Li-Mei Lin; Fu-Bao Gong; Shui-Yuan Chen; Gui-Lin Chen (Chemical Engineering Journal, 2026)

Rice SINA E3 ligases dichotomously control ERECTA1 ubiquitination and stability to regulate panicle morphogenesis and grain yield - Zi-Qi Lu; Tao Guo; Ying-Jie Cao; Jun-Xiang Shan; Wang-Wei Ye; Nai-Qian Dong; Yi Kan; Yi-Bing Yang; Shuang-Qin Guo; Jie-Jie Lei; Xiao-Rui Mu; Ji-Fu Zhou; et al. (Molecular Plant, 2026)

Malt endogenous amylase-hydrolyzed nanostarch for anthocyanin encapsulation by nanoprecipitation: Fabrication, characterization and evaluation - Shucheng Liu; Yanyun Lin; Xiaoyan Fu; Qiuyu Xia; Naiyong Xiao; Yang Liu; Rui Hai Liu; Wen Xia (Food Chemistry, 2026)

Corrigendum to “Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk” [Toxicology and Applied Pharmacology Volume 503, October 2025, 117465]. - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

Aluminum exposure disturbs epigenetic modification and organelle function during early embryo development - Xiao-Ting Yu; Zhen-Hui Fu; Wen-Lin Pan; Yan-Lun Song; Rui-Jie Ma; Hao-Lin Zhang; Xing-He Ke; Shao-Chen Sun; Jun-Li Wang; Lin-Lin Hu (Chemico-Biological Interactions, 2025)

Two new withanolides from Physalis minima L - Li-Jie Zhang; Mei-Lin Peng; Shi-Ying Xu; Fu-Rui Wang; Lin-Lin Yu; Qin-Feng Zhu; Shang-Gao Liao; Guo-Bo Xu (Natural Product Research, 2025)

Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

Dose effects of polyethylene microplastics on the degradation of phenanthrene in agricultural soils and its underlying mechanisms - Chengyue Liang; Weilian Fu; Lin Tian; Wumei Xu; Yong Zhang; Tai Xiang; Rui Xu (Journal of Environmental Chemical Engineering, 2025)

Multifunctional flexible multilayer pressure sensor for pressure sensing, energy harvesting and versatile applications - Fu-Rui Teng; Song Sun; Si-Chen Tan; Ying-Jie Ma; Yue Huang; Lin Zhu; Di Wu; Ai-Dong Li (Chemical Engineering Journal, 2025)

A rapid and efficient microenvironment improving hyaluronic acid microneedle dressing for burn wound synergistic treatment - Lin Lei; Wei Li; Jiajia Wang; Qi Liu; Feng Zeng; Yunqiang Xiang; Xinyuan Fu; Rui Tao; Zhangyou Yang (Carbohydrate Polymers, 2025)

A unique demersal fish fauna in the Chukchi Borderland, Central Arctic Ocean - Ran Zhang; Hai Li; Puqing Song; Rui Wang; Jing Zhang; Tianci Wang; Shusen Fu; Shigang Liu; Yuan Li; Xing Miao; Lei Yang; Longshan Lin (Reviews in Fish Biology and Fisheries, 2025)

Primary greisen-type tin mineralization: Insights from unidirectional solidification texture in oxidized, fluorine-rich ores from the Paleocene Kalonta Sn-W deposit, southern Myanmar - Jin-Xiang Li; Wei-Ming Fan; Rui Yuan; Lamu Ciren; Li-Yun Zhang; Fu-Long Cai; Ya-Hui Yue; Jing Xie; Lin Ding (Journal of Asian Earth Sciences, 2025)

Inorganic arsenic in aquatic products in Shenzhen, China from 2018 to 2024: Levels, temporal variation and health risk assessment - Bo Fu; Kai Lin; Sisi Yu; Yiming Ge; Xinjie Li; Wenchao Zhu; Lei Tan; Rui Wang; Jixi Ou; Shaoyou Lu (Food and Chemical Toxicology, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Study on seeding delay time and lag distance of automatic section control system for maize seeder - Lin Ling; Hanqing Li; Yuejin Xiao; Weiqiang Fu; Jianjun Dong; Liwei Li; Rui Liu; Xinguang Huang; Guangwei Wu; Zhijun Meng; Bingxin Yan (Computers and Electronics in Agriculture, 2025)

Experimental and Numerical Investigation on Mechanical Properties of Large-Diameter Metallurgically Clad Pipes - Feng Wang; Yanan Gao; Zhiguo Hu; Shuo Yang; Zhenying Cui; Rui Fu; Lin Yuan (Journal of Marine Science and Engineering, 2025)
Bimetallic-clad pipes demonstrate exceptional advantages in transporting corrosive oil and gas through the combination of the load-carrying capacity of the base material and the anti-corrosive function of the thin layer of corrosion-resistant alloy. This study investigates the mechanical properties of 24-inch X65 + Alloy625 metallurgically clad pipes through experimental tests and finite element analysis. Uniaxial tensile testing with digital image correlation reveals uniform deformation between the base and clad layers until interfacial failure initiates at an average strain threshold of 34.17%. Microstructural characterization shows continuous metallurgical bonding, with the X65 layer exhibiting polygonal ferrite and bainitic phases, contrasting with the austenitic equiaxed grain structure of Alloy625. In terms of numerical modeling, finite element analyses that consider both initial geometric imperfections and manufacturing-induced residual stresses are performed to evaluate the bending response of the clad pipe. The effect of initial ovality and residual stresses on its bending capacity is also studied.

Enhanced electron transport through hydrogen bonds and Ag nanoparticles in the PCN-222/Ag/COF core–shell photocatalyst for efficient oxytetracycline degradation - Bing-Bing Lu; Jia-Chang Lu; Qing-Yun Zhao; Rui Wang; Ze-Lin Chen; Ji-Qiang Guan; Hao Liu; Ying Fu; Fei Ye (Journal of Cleaner Production, 2025)

Improving the bactericidal activity of carvacrol against Bacillus cereus by the formation of sodium casein-stabilized nanoemulsion and its application in milk preservation - Jun Li; Fu-Yu Liu; Bao-Lin He; Rui Cui; Hong Wu (Food Hydrocolloids, 2025)

Black soldier fly larvae promote the resource of cyanobacteria: Frass-mixed compost - Rui Li; YuFeng Jiang; ChangXue Wang; Kai Luo; XiaoLei Fan; TianHui Lin; RongBo Guo; ShanFei Fu (Journal of Environmental Chemical Engineering, 2024)

Lymph nodes in oral squamous cell carcinoma: a comprehensive anatomical perspective - Guang-Rui Wang; Nian-Nian Zhong; Lei-Ming Cao; Xuan-Hao Liu; Zi-Zhan Li; Yao Xiao; Kan Zhou; Yi-Fu Yu; Bing Liu; Lin-Lin Bu (Clinical & Experimental Metastasis, 2024)

Unraveling the toxicity mechanisms of nanoplastics with various surface modifications on Skeletonema costatum: Cellular and molecular perspectives - Ting-Ting Xu; Zhen-Liang Li; Heng-Xiang Li; Lang Lin; Rui Hou; Shan Liu; Tao Li; Eddy Y. Zeng; Ke-Fu Yu; Xiang-Rong Xu (Science of The Total Environment, 2024)

Comprehensive investigation of daytime radiative cooling technology for sustainable grain storage: A combined approach of field measurement and CFD simulations - Chongjia Lin; Yunlong Wang; Zhihang Zhao; Xisheng Lin; Rui Li; Zhaoping Zheng; Xuhua Shen; Zhongqing Lang; Weizhi Zhou; Jinbei Wang; Dan Yuan; Yankai Sun; et al. (Building and Environment, 2024)

Protective effect of resveratrol on nickel-refining fumes-induced inflammatory damage - Yu-Lin Pan; Rui-Ze Wu; Yao Fu; Rui Xin; Yong-Hui Wu (Cell Biochemistry and Biophysics, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Effects of salinity in food waste on the growth of black soldier fly larvae and global warming potential analysis - Rui Li; TianHui Lin; XiaoLei Fan; XiaoFeng Dai; JieHua Huang; YiFeng Zhang; RongBo Guo; ShanFei Fu (Chemical Engineering Journal, 2024)

Westerly aridity in the western Tarim Basin driven by global cooling since the mid-Pleistocene transition - Hongye Liu; Rui Zhang; Yansheng Gu; Gaowen Dai; Lin Li; Shuo Guan; Zhongbiao Fu (Quaternary Science Reviews, 2023)

Analysis of the spatial-temporal evolution of Green and low carbon utilization efficiency of agricultural land in China and its influencing factors under the goal of carbon neutralization - Jun Fu; Rui Ding; Yu-qi Zhu; Lin-yu Du; Si-wei Shen; Li-na Peng; Jian Zou; Yu-xuan Hong; Juan Liang; Ke-xin Wang; Wen-qian Xiao (Environmental Research, 2023)

Magmatic fluids responsible for lode gold mineralization in the giant Linglong deposit at Jiaodong, North China Craton: Constraints from LiO isotopes - Shao-Rui Zhao; Zhan-Ke Li; Zu-Wei Lin; Jian-Feng Gao; Hua-Shan Sun; Martin Yan Hei Li; Xin-Fu Zhao (Chemical Geology, 2023)

The Effect of Water Spinach on the Water Quality, Antioxidant System, Non-Specific Immune Response, Growth Performance, and Carbon Balance in Red Tilapia Production - Yuan-Yuan Luo; Xian-Can Chen; Rui-Lin Xie; Zhuo-Hao Ruan; Zhi-Qiang Lu; Liang-Sen Jiang; Yi-Fu Li; Wen-Sheng Liu (Fishes, 2023)
In this study, the compound aquaculture model of red tilapia (O. mossambicus albina × O. urolepis hornorum) and water spinach (Ipomoea aquatica) was used to investigate the effect of water spinach rafts on the water quality, antioxidant system, non-specific immune response, and growth performance of red tilapia and the carbon balance of payments. Red tilapia is characterized by its high adaptability to different production environments and food sources, as one of the most productive fish in aquaculture, and is well accepted in the market due to its nutritional and organoleptic characteristics. The experiment lasted for nine weeks and included two systems: the red tilapia-water spinach raft aquaponics (AP) system with 10% cover ratio with water spinach floating beds, and the aquatic monoculture (AM) system with only red tilapia. The total phosphorus (TP), total nitrogen (TN), and nitrate nitrogen (NO−3-N) in the AM were higher than those in AP from the fifth to ninth week. On the second, third, fifth, and sixth weeks, the ammonia nitrogen (NH4+-N), in the AM was higher than those in the AP. From the seventh week, the pH of the AM was significantly lower than the AP, while the nitrite nitrogen (NO−2-N) was significantly higher than the AP. The water quality index of the AP was better than that of the AM, indicating that water spinach can remove the nutrients from aquaculture water bodies. The average daily gain and specific growth rate (SGR) of fish in AP were higher than those in the AM. The acid phosphatase (ACP), alkaline phosphatase (AKP), and catalase (CAT) activities in the hepatopancreas of red tilapia in the AP were also significantly higher than those in the AM, while the malondialdehyde (MDA) in the AP was lower than the AM. The serum ACP and CAT of red tilapia in the AP were also higher than those in the AM, while the MDA of fish in the AP was lower than the AM. The results showed that both the experimental group and the control group were carbon sources and released greenhouse gases into the atmosphere, but the total carbon emissions of the red tilapia and the water spinach symbiotic system in the experimental group was significantly lower than that of the control group (p

Anodic oxidation-accelerated self-reconstruction of tri-metallic Prussian blue analogue toward robust oxygen evolution reaction performance - Thi Xuyen Nguyen; Kai-Hsiang Yang; Yan-Jia Huang; Yen-Hsun Su; Oliver Clemens; Rui-Kun Xie; Yu-Jung Lin; Jyh-Fu Lee; Jyh-Ming Ting (Chemical Engineering Journal, 2023)

Highly stable and selective Pt/TS-1 catalysts for the efficient nonoxidative dehydrogenation of propane - Weilong Hou; Kehang Lin; Xiangyu Zhang; Bowen Xu; Yuexia Wang; Xinqing Lu; Yijing Gao; Rui Ma; Yanghe Fu; Weidong Zhu (Chemical Engineering Journal, 2023)

A novel starch-based ethanol gel with contact-killing bacteria to cut off contact transmission of bacteria - Fu-Xiang Wei; Tian-Rui Zhou; Shao-Wei Zhong; Yong-Fu Deng; Chuan-Hui Xu; Li-Hua Fu; Bao-Feng Lin (Chemical Engineering Journal, 2023)

Carbon source shaped microbial ecology, metabolism and performance in denitrification systems - Yuan Pan; Rui-Zhe Sun; Yan Wang; Guan-Lin Chen; Ying-Ying Fu; Han-Qing Yu (Water Research, 2023)

Two new bibenzyls from Pleione grandiflora (Rolfe) Rolfe and their antioxidant activity - Wei Li; Jia-Rui Fu; Li-Jun Zheng; Lin Ni; Jun-Qing Liu; Jun-Wen Zhai; Zhuang Zhou; Sha-Sha Wu (Natural Product Research, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Magnetic anaerobic granular sludge for sequestration and immobilization of Pb - Rui Zhou; Han Li; Chengshuai Liu; Yizhang Liu; Jyh-Fu Lee; Yu-Jung Lin; Zhang Yan; Zhangyi Xu; Xiaoyun Yi; Chunhua Feng (Water Research, 2023)

Molecular insights into the dissolved organic matter of leather wastewater in leather industrial park wastewater treatment plant - Xiao-Xu Gao; Yun-Wen Wang; Ye-Chen An; Rui-Yun Ren; Yao-Hui Lin; Ning Wang; Yi-Fan Wang; Jing-Long Han; Zhi-Neng Hao; Jing-Fu Liu; Ai-Jie Wang; Nan-Qi Ren (Science of The Total Environment, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

High entropy promoted active site in layered double hydroxide for ultra-stable oxygen evolution reaction electrocatalyst - Thi Xuyen Nguyen; Chia-Chien Tsai; Van Thanh Nguyen; Yan-Jia Huang; Yen-Hsun Su; Siang-Yun Li; Rui-Kun Xie; Yu-Jung Lin; Jyh-Fu Lee; Jyh-Ming Ting (Chemical Engineering Journal, 2023)

Short- and medium-chain chlorinated paraffins in urban road dust of Shanghai, China: concentrations, source apportionment and human exposure assessment - Xue-Tong Wang; Cheng-Lin Wang; Ying Zhou; Guo-Fa Ren; Rui Fu; Jing An (Environmental Geochemistry and Health, 2023)

An injectable and rapidly degraded carboxymethyl chitosan/polyethylene glycol hydrogel for postoperative antiadhesion - Meiyue Wang; Sen Lin; Mengzhe Liu; Jing Jiao; Hongyan Mi; Jingjing Sun; Yiming Liu; Ruiying Guo; Sirui Liu; Haojie Fu; Yanyu Yang; Rui Li (Chemical Engineering Journal, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Amorphous nanophosphates of dual-metal (Co and Ni) for the decomposition of ozone under humid conditions - Qian Zhang; Jifei Liao; Guangzhi Du; Yu Lin; Xiaoqiong Liu; Rui Wang; Lingyu Huang; Wenyan Xiao; Jiahao Chen; Yan Fu (Journal of Environmental Chemical Engineering, 2023)

A hybrid deep learning model for regional O3 and NO2 concentrations prediction based on spatiotemporal dependencies in air quality monitoring network - Cui-lin Wu; Hong-di He; Rui-feng Song; Xing-hang Zhu; Zhong-ren Peng; Qing-yan Fu; Jun Pan (Environmental Pollution, 2023)

Phosphorus availability mediates plant–plant interaction and field productivity in maize-grass pea intercropping system: Field experiment and its global validation - Shuang-Guo Zhu; Hong-Yan Tao; Wen-Bo Li; Rui Zhou; Yan-Wen Gui; Li Zhu; Xiao-Lin Zhang; Wei Wang; Bao-Zhong Wang; Fu-Jian Mei; Hao Zhu; You-Cai Xiong (Agricultural Systems, 2023)

Unique bacterial communities and lifestyles in deep ocean blue holes: Insights from the Yongle Blue Hole (South China Sea) - Shun Zhou; Jiwen Liu; Peng Yao; Liang Fu; Zuosheng Yang; Yulin Zhang; Rui Du; Chao Jia; Lin Chen; Jinchang Liang; Xiaolei Wang; Xiaochong Shi; et al. (Frontiers in Marine Science, 2023)
Deep ocean blue holes possess steep physicochemical gradients, especially low dissolved oxygen concentration, which shape the extraordinary microbial communities. However, the environmental responses of microorganisms with different lifestyles and knowledge of culturable microorganisms in the blue holes are still unknown. Here, we investigated the bacterial community structure with different lifestyles of the world’s deepest blue hole - the Yongle Blue Hole (YBH) in the South China Sea using both culture-dependent and -independent methods. YBH can be divided by oxygen content into an oxic zone, a suboxic zone and two anoxic zones. The abundance of bacteria, archaea, genes dsrB and soxB were all higher in the free-living (FL) lifestyle than in the particle-associated (PA) lifestyle, yet the diversity and richness of PA bacteria were higher than that of FL bacteria. More Gammaproteobacteria and less Alphaproteobacteria , Chloroflexi and Nitrospinae were observed within the FL fraction than within the PA fraction. The relative abundance of sulfur-oxidizing bacteria (SOB) was dominant between 100-140 m (anoxic zone I) in YBH, with a maximum of 90.0% (140 m FL fraction). The SOB in YBH were mainly colorless sulfur bacteria and purple non-sulfur bacteria, of which Thiomicrorhabdus and Sulfurimonas were the main representatives. In addition, a total of 294 bacterial strains were isolated on a variety of media and culture conditions, and 22.2% (18/81) of anaerobic strains were identified as potential novel species. Our study reveals a distinction between FL and PA bacteria in YBH. It contributes to further understanding of the bacterial community in deep ocean blue holes, and provides bacterial resources for subsequent studies on their adaptation to extreme marine environments.

Wastewater treatment by anodic oxidation in electrochemical advanced oxidation process: Advance in mechanism, direct and indirect oxidation detection methods - Rui Fu; Peng-Shuang Zhang; Yuan-Xing Jiang; Lin Sun; Xu-Hui Sun (Chemosphere, 2023)

Robust emission in near-infrared II of lanthanide nanoprobes conjugated with Au (LNPs-Au) for temperature sensing and controlled photothermal therapy - Guofeng Liu; Zhenxing Wang; Wan Sun; Xiaohui Lin; Rui Wang; Chonghui Li; Li Zong; Zuoling Fu; Hanping Liu; Shicai Xu (Chemical Engineering Journal, 2023)

Near-infrared I/II emission and absorption carbon dots via constructing localized excited/charge transfer state for multiphoton imaging and photothermal therapy - Wen-Bo Zhao; Dan-Dan Chen; Kai-Kai Liu; Yong Wang; Rui Zhou; Shi-Yu Song; Fu-Kui Li; Lai-Zhi Sui; Qing Lou; Lin Hou; Chong-Xin Shan (Chemical Engineering Journal, 2023)

Occurrence, source apportionment, and carcinogenic risk assessment of polycyclic aromatic hydrocarbons in urban road dusts in Shanghai - Xue-Tong Wang; Rui Fu; Ying Zhou; Cheng-Lin Wang; Guo-Fa Ren; Xiao-Li Wang; Hui Li (Environmental Science and Pollution Research, 2021)

Chemical constituents from the barks of Melia azedarach and their PTP1B inhibitory activity - Sheng-Nan Zhang; Lin Huang; Rui-Jing Ma; Mei-Feng Yang; Ben-Fu Wei; Hong-Zhi Song; Heng-Shan Wang; Qin-Gang Tan (Natural Product Research, 2021)

The geochemical behavior of trace metals and nutrients in submerged sediments of the Three Gorges Reservoir and a critical review on risk assessment methods - Bin Wang; Shu Chen; Yuwei Chen; Nelson Belzile; Rui Zheng; Yuankun Yang; Kaibin Fu; Yongcan Chen; Binliang Lin; Zhaowei Liu; Jian Sun (Environmental Science and Pollution Research, 2021)

The substrate‐dependent regulatory effects of the AfeI /R system in Acidithiobacillus ferrooxidans reveals the novel regulation strategy of quorum sensing in acidophiles - Xue‐Yan Gao; Chang‐Ai Fu; Likai Hao; Xiu‐Feng Gu; Rui Wang; Jian‐Qiang Lin; Xiang‐Mei Liu; Xin Pang; Cheng‐Jia Zhang; Jian‐Qun Lin; Lin‐Xu Chen (Environmental Microbiology, 2021)
Summary A LuxI/R‐like quorum sensing (QS) system (AfeI/R) has been reported in the acidophilic and chemoautotrophic Acidithiobacillus spp. However, the function of AfeI/R remains unclear because of the difficulties in the genetic manipulation of these bacteria. Here, we constructed different afeI mutants of the sulfur‐ and iron‐oxidizer A . ferrooxidans , identified the N‐acyl homoserine lactones (acyl‐HSLs) synthesized by AfeI, and determined the regulatory effects of AfeI/R on genes expression, extracellular polymeric substance synthesis, energy metabolism, cell growth and population density of A . ferrooxidans in different energy substrates. Acyl‐HSLs‐mediated distinct regulation strategies were employed to influence bacterial metabolism and cell growth of A . ferrooxidans cultivated in either sulfur or ferrous iron. Based on these findings, an energy‐substrate‐dependent regulation mode of AfeI/R in A . ferrooxidans was illuminated that AfeI/R could produce different types of acyl‐HSLs and employ specific acyl‐HSLs to regulate specific genes in response to different energy substrates. The discovery of the AfeI/R‐mediated substrate‐dependent regulatory mode expands our knowledge on the function of QS system in the chemoautotrophic sulfur‐ and ferrous iron‐oxidizing bacteria, and provides new insights in understanding energy metabolism modulation, population control, bacteria‐driven bioleaching process, and the coevolution between the acidophiles and their acidic habitats.

Os4BGlu14, a monolignol β-Glucosidase, negatively affects seed longevity by influencing primary metabolism in rice - Rui-Juan Ren; Pei Wang; Li-Na Wang; Jing-Ping Su; Lin-Jing Sun; Yue Sun; De-Fu Chen; Xi-Wen Chen (Plant Molecular Biology, 2020)

3D-QSAR, HQSAR, molecular docking, and new compound design study of 1,3,6-trisubstituted 1,4-diazepan-7-ones as human KLK7 inhibitors - Le Fu; Yi Chen; Chun-mei Xu; Tao Wu; Hong-mei Guo; Zhi-hua Lin; Rui Wang; Mao Shu (Medicinal Chemistry Research, 2020)

Microsatellite records for volume 10, issue 1 - Ai-Qing Yu; Chengxin Fu; Chongbo He; Fei Liu; Guo-Hua Ding; Hongman Hou; Jian Zhao; Jianmin Yang; Jiansheng Wang; Kun-ci Chen; Lan-lan Zhang; Pan Li; et al. (Conservation Genetics Resources, 2018)

Expression-based genotyping of the rice blast resistance genes in the elite maintainer line Yixiang1B - Li Wang; Xiao-Hong Hu; Gang Lin; De-Ming Zhao; Jun Shi; Zhi-Xue Zhao; Rui Zeng; Heng-Jing Li; De-Qiang Li; Jing Fan; Yan Li; Fu Huang; et al. (European Journal of Plant Pathology, 2017)

Mechanism Underlying the Analgesic Effect Exerted by Endomorphin-1 in the rat Ventrolateral Periaqueductal Gray - Tao Chen; Jing Li; Ban Feng; Rui Hui; Yu-Lin Dong; Fu-Quan Huo; Ting Zhang; Jun-Bin Yin; Jian-Qing Du; Yun-Qing Li (Molecular Neurobiology, 2016)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Gastrin inhibits a novel, pathological colon cancer signaling pathway involving EGR1, AE2, and P-ERK - Ling-Jun Song; Rui-Jun Liu; Zhi Zeng; Seth L. Alper; Heng-Jing Cui; Yang Lu; Lin Zheng; Zhao-Wen Yan; Guo-Hui Fu (Journal of Molecular Medicine, 2012)

Genome sequence and characterization of a new virus infecting Mikania micrantha H.B.K. - Rui-Long Wang; Ling-Wen Ding; Qiao-Yang Sun; Jing Li; Zeng-Fu Xu; Shao-Lin Peng (Archives of Virology, 2008)